Sugarcane in Bihar A boon for small and marginal farmers - Pandey, S S; Thakur, S K; Kamat, D N (Indian Farming, 2017)
Sugar industry in Bihar plays a prominent role in it’s economy. This industry generates sizeable employment in the farm sector directly as well as through ancillary industries and related activities. It is estimated that about five lakh farmers and their dependents are engaged in the cultivation of sugarcane and approximately another half a lakh unskilled and skilled personnel, including highly qualified and trained technologists are engaged in the sugar industry in the state.